2019
DOI: 10.1021/acs.jmedchem.8b01781
|View full text |Cite|
|
Sign up to set email alerts
|

Antibiotic Adjuvants: Make Antibiotics Great Again!

Abstract: During the last decades, multiple approaches have been developed to combat bacterial resistance.However, the combination of antibiotic resistance mechanisms by bacteria and the limited number of effective antibiotics available, decreases the number of the interventions for the treatment of current bacterial infections. The solution to emerging antibiotic resistance will likely involve combination therapies of existing antibiotics and smart adjuvants, which re-empower the antibiotic agent to become efficacious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
166
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(170 citation statements)
references
References 116 publications
0
166
0
4
Order By: Relevance
“…Recent study has demonstrated that efflux pump inhibitors, including N-acetylcysteine, Tris-EDTA, and disodium EDTA have intrinsic antimicrobial activity and overcome antibiotic resistance. These AA could be used to enhance the efficacy of existing antibiotics against Gram-negative and multidrug-resistant bacteria [ 140 , 141 ]. Thus, AA provide an economical alternative to time-consuming and costly development of new antibiotics targeting antibiotic resistance.…”
Section: Alternative Strategies To Combat Antibiotic Resistancementioning
confidence: 99%
“…Recent study has demonstrated that efflux pump inhibitors, including N-acetylcysteine, Tris-EDTA, and disodium EDTA have intrinsic antimicrobial activity and overcome antibiotic resistance. These AA could be used to enhance the efficacy of existing antibiotics against Gram-negative and multidrug-resistant bacteria [ 140 , 141 ]. Thus, AA provide an economical alternative to time-consuming and costly development of new antibiotics targeting antibiotic resistance.…”
Section: Alternative Strategies To Combat Antibiotic Resistancementioning
confidence: 99%
“…They have per se no (or only a limited) antibacterial activity but they nevertheless potentiate the effect of antibiotics. [8][9][10][11] Another mechanism of therapy evasion consists of emergence of a small subpopulation of nondividing persister cells in a growing microbial population. [12][13][14][15][16][17][18] Persister cells are by definition insensitive (tolerant) to antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the scarcity of available therapeutic options, novel strategies have been proposed to combat bacterial pathogens more effectively [11,12]. One of these strategies is combination therapy with the use of existing antibiotics, however, except for some well-defined clinical situations, the clinical utility of antibiotic combinations has been controversial, in addition to their costs for the healthcare infrastructure [13].…”
Section: Introductionmentioning
confidence: 99%
“…One of these strategies is combination therapy with the use of existing antibiotics, however, except for some well-defined clinical situations, the clinical utility of antibiotic combinations has been controversial, in addition to their costs for the healthcare infrastructure [13]. Another possible therapeutic alternative is to utilize adjuvant compounds (together with antibiotics) during therapy [12,14]. These antimicrobial adjuvants are classified to two distinct categories: Class I adjuvants affect the microorganism, while Class II adjuvants affect the cells of the host.…”
Section: Introductionmentioning
confidence: 99%